Determinan Islamic Social Reporting Pada Perusahaan Yang Terdaftar Di Jakarta Islamic Index Tahun 2017-2019 - Muhammad Afif Setyawan (Jurnal Ekonomika dan Bisnis, 2022)
Muhammad Afif Setyawan. Determinants of Islamic Social Reporting in Companies Listed in the Jakarta Islamic Index 2017-2019. Faculty of Economics. D3 Accounting Study Program. Nahdlatul Ulama University, Surakarta. 2022. 17 pages. The number of companies listed on the Jakarta Islamic Index as the sample of this study were 30 companies with an observation period of 3 years. Based on the purposive sampling research method, there were 16 companies that met the criteria so that the data processed were 48 data. The results showed that partially Profitability, Liquidity, Leverage, and Company Age had no effect on Islamic Social Reporting. While the size of the company has an effect on Islamic Social Reporting. The results showed that simultaneously Profitability, Liquidity, Leverage, Company Size and Company Age had an effect on Islamic Social Reporting.